The First Temporal and Spatial Assessment of Vibrio Diversity of the Surrounding Seawater of Coral Reefs in Ishigaki, Japan - Amin, A.K. M. R.; Feng, Gao; Al-saari, Nurhidayu; Meirelles, Pedro M.; Yamazaki, Yohei; Mino, Sayaka; Thompson, Fabiano L.; Sawabe, Toko; Sawabe, Tomoo (Frontiers in Microbiology, 2016)
Coral reefs perform a major role in regulating marine biodiversity and serve as hotspot for highly dynamic and diverse microbiomes as holobionts. Corals around Ishigaki, however, are at risk due to tremendous stressors including elevation of seawater temperature, eutrophication and so on. However, no information is currently available on how Vibrio diversity fluctuates spatially and temporally due to environmental determinants in Ishigaki coral reef ecosystems. The aim of this study is to elucidate spatiotemporal Vibrio diversity dynamic at both community and population levels and to assess the environmental drivers correlated to Vibrio abundance and diversity. The Vibrio community identified based on pyrH gene phylogeny of 685 isolates from seawater directly connecting to Ishigaki coral holobionts consisted of 22 known and 12 potential novel Vibrionaceae species. The most prominent species were V. hyugaensis, V. owensii and V. harveyi followed by V. maritimus/V. variabillis, V. campbellii, V. coralliilyticus and P. rosenbergii. The Vibrio community fluctuations, assessed by PCoA with UniFrac distance and clustering with Euclidiean distance were varied less not only by year but also by site. Interestingly, significant positive correlation was observed between rising seawater temperature and the abundance of V. campbellii (r=0.62; P<0.05) whereas the opposite was observed for V. owensii (r=-0.58; P<0.05) and the C6 group of V. hyugaensis (r=-0.62; P<0.05). AdaptML-based microhabitat differentiation revealed that V. harveyi, V. campbellii, P. rosenbergii and V. coralliilyticus populations were less-ecologically distinctive whereas V. astriarenae and V. ishigakensis were ecologically diverse. This knowledge could be important clue for the future actions coral conservation.